Case Report: Primary Diffuse Leptomeningeal Oligodendrogliomatosis in a Young Adult Cat - Chludzinski, Elisa; Puff, Christina; Weber, Jürgen; Hewicker-Trautwein, Marion (Frontiers in Veterinary Science, 2021)
A 2-year-old cat was presented with progressive ataxia. Despite treatment the animal died. Pathomorphological examination revealed a widespread leptomeningeal mass at all levels of the central nervous system accentuated on the cervical spinal cord and the medulla oblongata without presence of a primary intraaxial tumor. The neoplasm was mainly composed of round, uninucleate cells with hyperchromatic nuclei, which were immunopositive for OLIG2, doublecortin, MAP2, synaptophysin, and vimentin, indicating components of both oligodendroglial and neuronal differentiation. Ki-67 immunohistochemistry indicated a high proliferation activity of the neoplasm. Few GFAP positive and Iba-1 positive cells were interpreted as reactive astrocytes and macrophages or microglia, respectively. The tumor was immunonegative for CD3, CD20, PAX5, MUM1, pan-cytokeratin, S100, NSE, p75NTR, NeuN and periaxin. These findings led to the diagnosis of primary diffuse leptomeningeal oligodendrogliomatosis. This is the first reported case of this entity in a young cat, which should be considered as a differential diagnosis for diffuse subarachnoidal round cell infiltrates.